2015
DOI: 10.1007/s10750-015-2278-1
|View full text |Cite
|
Sign up to set email alerts
|

Species area relationship (SAR) for benthic diatoms: a study on aquatic islands

Abstract: 19The question of how species richness depends on the area is one of the most intensively 20 studied subjects in biogeography. Many studies reported this pattern for terrestrial and 21 macroscopic taxa, however microscopic and aquatic communities received much less 22 attention in the literature. The aim of our study was to reveal the relationship between the 23 habitat size and the richness of freshwater benthic diatom assemblages. We hypothesized that 24 if the size of studied water bodies covers wide spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…In a seminal paper by Patrick (), factors behind SARs in stream diatoms were studied, and findings suggested that species richness is influenced by the invasion rate, area, and the number of species in the species pool. In one of the few more recent studies about diatom SARs, Teittinen and Soininen () did not find a significant SAR in spring diatoms, whereas Bolgovics, Ács, Várbíró, Görgényi, and Borics () demonstrated that among lakes, ponds and pools, diatom richness increased with area. Thus, we think that much remains to be studied about SARs in benthic diatoms since even the generality of the pattern in different ecosystems is poorly resolved let alone the actual mechanism behind the SAR in diatoms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a seminal paper by Patrick (), factors behind SARs in stream diatoms were studied, and findings suggested that species richness is influenced by the invasion rate, area, and the number of species in the species pool. In one of the few more recent studies about diatom SARs, Teittinen and Soininen () did not find a significant SAR in spring diatoms, whereas Bolgovics, Ács, Várbíró, Görgényi, and Borics () demonstrated that among lakes, ponds and pools, diatom richness increased with area. Thus, we think that much remains to be studied about SARs in benthic diatoms since even the generality of the pattern in different ecosystems is poorly resolved let alone the actual mechanism behind the SAR in diatoms.…”
Section: Introductionmentioning
confidence: 95%
“…The interspecific abundance-occupancy relationship (Brown, 1984) is one of the most classical topics in macroecology and widely documented for many larger taxa such as plants, birds, invertebrates, and fish from various types of ecosystems (Blackburn, Cassey, & Gaston, 2006).…”
Section: Interspecific Abundance-occupancy Relationships In Diatomsmentioning
confidence: 99%
“…Furthermore, landscape-related factors, such as topography or ecoregion type, may also affect aquatic micro-organisms because they integrate ecological factors that influence species composition and diversity directly or indirectly (Pan, Stevenson, Hill, & Herlihy, 2000;Reche, Pulido-Villena, Morales-Baquero, & Casamayor, 2005;Rocha, Heino, Machado-Velho, Lansac-Tôha, & Lansac-Tôha, 2017). Habitat connectivity has been shown to be an important factor for maintaining ecological communities, in which community composition is likely to be richer in areas that facilitate dispersal and colonization (Bolgovics, Ács, Várbíró, Görgényi, & Borics, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the huge amount of information accumulated in this field, most of our knowledge on SARs is based on analyses of macroscopic, terrestrial systems. Aquatic and especially microbial examples are rare in the literature (Bolgovics, Ács, Várbíró, Görgényi, & Borics, 2016;Fenchel & Finlay, 2005;Fierer & Jackson, 2006;Smith et al, 2005). The model framework of SAR for terrestrial systems is commonly based on the principles of island biogeography.…”
mentioning
confidence: 99%
“…Thus, the investigation of well-isolated aquatic islands is a promising opportunity to test biogeographic theories. Although aquatic systems provide habitats for various groups of microscopic organisms (bacterio-, phyto-, and zooplankton, benthic algae), these groups have received limited attention in SAR analyses so far (Bolgovics et al, 2016;Dolan, 2005) partly because of methodological difficulties (sampling, definition, and identification of species) (Rodríguez-Ramos, Dornelas, Marañón, & Cermeño, 2014). Soininen found in a subarctic rock pool system that phytoplankton richness is related to nutrient availability, rather than to pool size (Soininen & Meier, 2014).…”
mentioning
confidence: 99%